The transformation of Canada's temporary foreign worker program - Ian O'Donnell; Mikal Skuterud (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2021)
Despite repeated efforts to curtail its size, we show that Canada's Temporary Foreign Worker (TFW) Programs have undergone a transformation since 2000, in which TFWs now account for nearly three percent of total Canadian employment - a six-fold increase - and are increasingly skilled, employed on long-term permits, and likely to transition to permanent residency (PR). While TFW entries that are labour market tested appear to be meeting genuine labour shortages, 85 percent are exempt from labour market tests (LMTs) and the growth in LMT-exempt permits has exceeded the growth in TFWs who transition to PR status. We argue that the system requires greater transparency in identifying the locations and occupations of TFWs with LMT-exempt permits and in tracking their PR transition rates.
Keywords: 330